PFM.48 Comparison of MRI and ultrasound to detect fetal macrosomia at term: a systematic review and meta-analysis. (9th June 2014) - Malin, GL; Bugg, GJ; Takwoingi, Y; Thornton, J; Jones, NW
Abstract : Background: Fetal macrosomia is associated with a number of complications, including shoulder dystocia and maternal and fetal birth trauma. Two dimensional ultrasound biometry has been shown to be inaccurate in diagnosing macrosomia. We performed a systematic review to compare 2D ultrasound with 3D and MRI methods. Methods: Systematic review of the literature, with bivariate meta-analysis of sensitivity, specificity and positive (LR +ve) and negative likelihood ratios (LR-ve), with 95% confidence intervals (CI), for macrosomia. Results: 46 studies were included. 25 studies (20591 women) used estimated fetal weight (EFW) calculated with the Hadlock formula. Using any definition of macrosomia, this gave a sensitivity of 0.58 (95% CI 0.54 to 0.63) and specificity of 0.93 (95% CI 0.90 to 0.94), LR +ve 7.86 (6.17 to 10.02) and LR-ve 0.45 (0.41 to 0.49). 8 studies (4546 women) used Hadlock EFW > 90 th centile to predict birth weight > 90 th centile; the sensitivity was 0.49 (95% CI 0.39 to 0.59), and specificity 0.92 (95% CI 0.86 to 0.95). 3 studies (117 women) used MRI EFW > 90 th centile to predict birth weight > 90 th centile with summary sensitivity 0.82 (95% CI: 0.60 to 0.95) and specificity 0.98 (0.92 to 1.00). One study (200 women) used 3D ultrasound volumetry to predict macrosomia, with a sensitivity of 0.42 and specificity 0.98. Conclusion: MRI appears to be more accurate than 2D or 3D ultrasound for detection of fetal macrosomia, but this is based on relatively few measurements. We plan a diagnostic accuracy study to investigate this further.